2008
DOI: 10.3354/meps07203
|View full text |Cite
|
Sign up to set email alerts
|

Life strategies of fishes in European estuaries: the functional guild approach

Abstract: The structure and functioning of estuarine fish assemblages have been analysed using data sets for 38 transitional waters covering all European latitudes, including NE Atlantic estuaries, Mediterranean lagoons and Scandinavian fjords. The fish species were assigned to functional guilds covering estuarine use, mode of feeding and reproductive strategy, thus describing the use made of transitional waters by fishes. The importance of estuaries as temporary biotopes (migration and nursery routes) for fish species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(150 citation statements)
references
References 39 publications
(49 reference statements)
11
126
0
5
Order By: Relevance
“…Our interpretations suggest that European flounder is not an exclusively catadromic species (e.g. Summers 1979, Franco et al 2008. The estuarine spawning of flounder has to be confirmed by sampling eggs in the different habitats within the river basins.…”
Section: Location Of Flounder Spawning Environmentsmentioning
confidence: 83%
See 2 more Smart Citations
“…Our interpretations suggest that European flounder is not an exclusively catadromic species (e.g. Summers 1979, Franco et al 2008. The estuarine spawning of flounder has to be confirmed by sampling eggs in the different habitats within the river basins.…”
Section: Location Of Flounder Spawning Environmentsmentioning
confidence: 83%
“…Although no other studies have definitively shown that the species exhibits this behavior, it is widely accepted (e.g. Borsa et al 1997, Minier et al 2000, Marchand et al 2003, Franco et al 2008. However, there has been no broad-scale, multi-site study showing the existence of a generalized catadromous strategy across the entire distribution range of the species.…”
Section: Age Of Flounder When Migrating To Freshwater Habitatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small sized-fish (resident and juvenile transient species) were sampled using a small hand-towed trawl net (length 3.5 m; mesh size 3 mm) and large-sized ones (adult transient fish) with a trammel net (length 10 m; mesh size 4.3-17 cm). Fishes were classified into estuarine use functional groups (i.e., resident and transient) according to Franco et al (2008). Due to their greater swimming ability and mobility compared with resident fish, adult transient fish were collected in random sites within the Stagnone di Marsala basin and considered as descriptors that integrate information from the whole area.…”
Section: Sample Collection and Processingmentioning
confidence: 99%
“…The European flounder (Platichthys flesus; Pisces, Pleuronectidea) is a demersal fish, with a wide distribution (from Norway to Portugal, Mediterranean, Baltic, North White and Black seas) (Morais et al, 2011), being present in both coastal waters and estuarine ecosystems (Vasconcelos et al, 2008). This species is among the most important components of estuarine fish assemblages in temperate latitudes (Franco et al, 2008;Martinho et al, 2010). P. flesus was chosen for this study due to its easy sampling and high ecological and economic relevance.…”
Section: Introductionmentioning
confidence: 99%